Prediction of UHPFRC panels thickness subjected to aircraft engine impact. (June 2016) - Thai, Duc-Kien; Kim, Seung-Eock
Highlights: The FE model of aircraft engine impact into UHPFRC panels were developed. The test results was used for the verification of numerical analysis. A parametric study was performed to investigate the local damage of the UHPFRC panels. The modified equations of Chang and Degen were proposed to predict the wall thickness. Abstract: In the practical design of nuclear building structures subjected to an aircraft crash, the structures are required to prevent scabbing and perforation. NEI 07-13 provided the formulas to predict the minimum reinforced concrete (RC) wall thickness to prevent the local damage caused by aircraft engine impact. However, these formulas may not be suitable for predicting the thickness of the ultra-high performance fiber reinforced concrete (UHPFRC) wall. In this study, the local damage of a UHPFRC wall caused by the impact of aircraft engine missile is investigated using a finite element program LS-DYNA. The structural components of the UHPFRC panel, aircraft engine model, and their contacts are fully modeled. The analysis results are verified with the test results. A parametric study with varying panel thickness, fiber type and content, and impact velocity is performed to investigate the local damage of the UHPFRC panel. Based on a comparison with the given formulas, the modified equations of Chang and Degen are proposed to predict the minimum wall thickness to prevent scabbing and perforation in the case in which the UHPFRC structure is used.